Empowering women for reducing radicalization in Indonesia - Safina, Firda; Nugroho, Alih Aji (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
The purpose of this research is to investigate the possibilities of localised female empowerment as a factor supporting deradicalization in Indonesia. Researchers look into the possibilities for deradicalization through localised empowerment of women using descriptive qualitative research methods. Descriptive research means collecting all data related to incidents or situations aligned with the study's theme. That is, by reading and analysing literature sources from regional journals, international articles, and online news sources that discuss women's participation in terrorist acts, women's empowerment in preventing terrorism initiatives, and existing attempts to eradicate terrorism in Indonesia. Using the data or information that has been found, researchers may use the grounded theory technique to explain the causes of a phenomenon, identify its causes and effects, and decide what actions can be implemented in regard to the current situation. The use of localised women's empowerment is thought to have the potential to be an preventative action against the issue of terrorism. Women may be incredibly motivating role models. Women are capable of doing this in the smallest scope, which is the family. Women are able to educate their children and families, provide the concept of tolerance, and spread the love of peace. That is why it is needed to strengthen the laws that may regulate existence of efforts to create deradicalization in local level by involving women in it.